2022
DOI: 10.1109/access.2022.3166509
|View full text |Cite
|
Sign up to set email alerts
|

Wide-Angle Ceramic Retroreflective Luneburg Lens Based on Quasi-Conformal Transformation Optics for Mm-Wave Indoor Localization

Abstract: This paper presents a quasi-conformal transformation optics (QCTO) based three-dimensional (3D) retroreflective flattened Luneburg lens for wide-angle millimeter-wave radio-frequency indoor localization. The maximum detection angle and radar cross-section (RCS) are investigated, including an impedance matching layer (IML) between the lens antenna and the free-space environment. The 3D QCTO Luneburg lenses are fabricated in alumina by lithography-based ceramic manufacturing, a 3D printing process. The manufactu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 66 publications
0
20
0
1
Order By: Relevance
“…3D printed ceramics are widely used for antenna applications, e.g. dielectric resonator antenna (DRA) [20]- [23], GRIN lens [24], and dielectric waveguide-based antennas [25], [26]. Zirconia (ZrO 2 ), the primary material used in this paper, is a technical ceramic with high permittivity that has recently been printed with near-full density using a nanoparticle jetting (NPJ) technique [27]- [29].…”
Section: Introductionmentioning
confidence: 99%
“…3D printed ceramics are widely used for antenna applications, e.g. dielectric resonator antenna (DRA) [20]- [23], GRIN lens [24], and dielectric waveguide-based antennas [25], [26]. Zirconia (ZrO 2 ), the primary material used in this paper, is a technical ceramic with high permittivity that has recently been printed with near-full density using a nanoparticle jetting (NPJ) technique [27]- [29].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, several designs have been reported in the literature to support these factors [10]- [22]. In [10], without the use of a retro-reflector, three Dielectric Resonator (DR) linear arrays were arranged to allow coding of 3-bits (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Third, there is additional effort to design rod antennas as coupling elements between the lens and PhC resonators. A solution toward sparing the need of these rods is proposed in [22] by using quasi-conformal transformation optics to build a flattened lens. However, the lens has been tested with a metallic reflector instead of a coding particle.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that the hypothetical deformation could be embodied into a material within a physical space using the TO method. TO has been used to create various devices with unique functions, including beam expanders (Rahm et al, 2008;Emiroglu and Kwon, 2010), polarization splitters and transformers (Kwon and Werner, 2008;Mousavi et al, 2017;Eskandari et al, 2018), waveguide couplers (García-Meca et al, 2011;Markov et al, 2012;Eskandari et al, 2017bEskandari et al, ,a, 2019bEskandari and Tyc, 2019), and directivity enhancers (Eskandari et al, 2021a,b;Schmiele et al, 2010;Yao and Jiang, 2011;Gu et al, 2012;Aghanejad et al, 2012;Wu et al, 2013;Giddens and Hao, 2020;Eskandari, 2022;Kadera et al, 2022;Nazarzadeh and Heidari, 2022).…”
Section: Introductionmentioning
confidence: 99%